PORTRAYING INTELLECTUAL DISABILITY AND ABLEISM IN THE NOVEL “FLOWER FOR ALGERNON” WRITTEN BY DANIEL KEYES - Yanti, Cita Hikmah; Anzar, Adenin (English Community Journal, 2024)
This research analyzes the representation of intellectual disability and ableism in the novel “Flowers for Algernon” by Daniel Keyes. The focus of this research is one the main character, Charlie Gordon, who experiences intellectual disability as well as the actions of ableism towards him. This research uses a qualitative method with a text analysis approach to explore how intellectual disability and ableism are portrayed in this novel. The results show that the novel effectively portrays the systemic discrimination and prejudice faced by individuals with intellectual disabilities, as well as highlighting the importance of inclusivity and respect for differences. This research contributes to a deeper understanding of the social impact of ableism and encourages advocacy for the rights and full inclusion of individuals with disabilities.